AN ANALYSIS OF HOMONYMY USED IN TANJUNG BELIT DIALECT: A SEMANTICS STUDY - Anzela, Meli; Oktariza, Dodi; Efendi, Dedi (Universitas Muara Bungo, 2024)
The writer analyses the words contain by homonymy used in Tanjung Belit dialect using a semantic study. The purpose of this research is to find out the kinds and explain the meaning of homonymy used in Tanjung Belit dialect. This analysis uses a descriptive qualitative research as a method and it has three procedures; they are collecting the data, analysing the data and data presentation. In collecting the data, the writer uses the participant observational method. In technique of collecting the data, the writer uses interview and note taking technique. In analysing of the data, the writer uses Sudaryanto's theory that is distributional and translational technique. The last procedure is data presentation, where the data is presented by using the informal method by Sudaryanto. The result of this analysis is that the writer found fifteen data included in homonymy in the Tanjung Belit dialect. In the fifteen datum that have been analyzed the writer is dominated by complete homonymy